PENGARUH FASILITAS LABORATORIUM DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR KOMPUTER AKUNTANSI - Subowo, -; Utomo, Dwi Budi (Fakultas Ekonomi, Universitas Negeri Semarang, 2009)
The objectives of the studyÃ‚Â areto know whether there are any influence of laboratory facilities and learning motivation toward studentsÃ¢â‚¬â„¢ achievement in Computer Accounting forÃ‚Â XII grade AccountingÃ¢â‚¬â„¢s Students in SMK Negeri 9 Semarang or not and to know the percentage of it.Population of this study was all students of XII grade Accounting Program in SMK Negeri 9 Semarang, the number were 82 students. The sample was all population involved Class Accounting I and Class Accounting II. Variables were laboratory facilities and learning motivation as independent variables and learning achievement in Accounting Computer as a dependent variable. Collecting the data used questionnnaire method and documentation, then analyzed byÃ‚Â percentage descriptive analysis and double- regression technique. Result of study showed there was a significant influence between laboratory facilities and learning motivation toward learning achievement in Accounting Computer, with regression equalityY = 23,540 + 0,503X1 + 0,178X2. From the data analysis, it was obtained Fhitungwas 150,299 higher than Ftabel = 3,112. It mean that hypothesis that statedthere was a significant influence between laboratory facilities and learning motivation toward learning achievement in Accounting Computer was accepted. Meanwhile, determination coefisien for R was 0,890 that showed that both laboratory facilities and learning motivation can influence learning achievement in Accounting Computer for 79.2%.Based on the result above, it is suggested for the schools to create a sufficient computer laboratory facilities and supporting books so students will get easy to study and can improve studentsÃ¢â‚¬â„¢ achievement learning, for teachers and parents to give motivation for students so they can be motivated to study in improving learning achievement. Key words : Laboratory Facilities, Learning Motivation, Learning Achievement